Barriers to the Implementation of Dental Insurance in Indonesia as Perceived by Primary Dentists - Iwan Dewanto; Sitichai Koontongkaew; Niken Widyastuti (Indonesian Dental Association, 2018)
Introduction: In 2014, the government of Indonesia launched the National Health Insurance (NHI) system. The system faced challenges in terms of its implementation because it changed the funding scheme within the pre-established health services structure. Under the new NHI system, the funding scheme for primary care providers is a capitation system; in the field of dental care, this means primary dentists received payment based on the amount number of participants enrolled within their geographical area. Objectives: The aim of this study is to describe primary dentists’ perceived constraints toward the implementation of the NHI system and their level of knowledge about managed care in Yogyakarta, Indonesia. Methods: To determine dentists’ perceptions about the implementation of NHI and their knowledge about managed care, we surveyed dentists in a descriptive study. Two types of questionnaire were administered to 91 dentists who work at community health centers (CHCs) in Yogyakarta, using the total population sampling technique. Result: Through the surveys, we determined that 78 dentists (71%) perceived constraints related to capitation, 65 dentists (72%) perceived constraints related to benefits packages, 59 dentists (65%) perceived constraints related to workload, and 23 dentists (25%) perceived constraints related to dental health facilities. In terms of their knowledge of managed care, 46 respondents (50.5%) demonstrated a good knowledge of managed care, 43 respondents (47.3%) had moderate knowledge, and 2 respondents (2.2%) had poor knowledge. Conclusion: The constraints to managed care, as perceived by primary dentists, should be taken into account when implementing the NHI system in Yogyakarta, as these perceptions could affect the system’s success.